MTCH2 is a conserved regulator of lipid homeostasis. Issue 3 (27th January 2017) - Rottiers, Veerle; Francisco, Adam; Platov, Michael; Zaltsman, Yehudit; Ruggiero, Antonella; Lee, Siu Sylvia; Gross, Atan; Libert, Sergiy
Abstract : Objective: More than one‐third of U.S. adults have obesity, causing an alarming increase in obesity‐related comorbidities such as type 2 diabetes. The functional role of mitochondrial carrier homolog 2 (MTCH2), a human obesity‐associated gene, in lipid homeostasis was investigated in Caenorhabditis elegans, cell culture, and mice. Methods: In C. elegans, MTCH2/MTCH‐1 was depleted, using RNAi and a genetic mutant, and overexpressed to assess its effect on lipid accumulation. In cells and mice, shRNAs against MTCH2 were used for knockdown and MTCH2 overexpression vectors were used for overexpression to study the role of this gene in fat accumulation. Results: MTCH2 knockdown reduced lipid accumulation in adipocyte‐like cells in vitro and in C. elegans and mice in vivo . MTCH2 overexpression increased fat accumulation in cell culture, C. elegans, and mice. Acute MTCH2 inhibition reduced fat accumulation in animals subjected to a high‐fat diet. Finally, MTCH2 influenced estrogen receptor 1 (ESR1) activity. Conclusions: MTCH2 is a conserved regulator of lipid homeostasis. MTCH2 was found to be both required and sufficient for lipid homeostasis shifts, suggesting that pharmacological inhibition of MTCH2 could be therapeutic for treatment of obesity and related disorders. MTCH2 could influence lipid homeostasis through inhibition of ESR1 activity.